PENGARUH APLIKASI CANVA TERHADAP KREATIVITAS DESAIN KOMUNIKASI VISUAL PADA MAHASISWA MAGANG SCTV 2023 - Annisa Nur Amini; Budi Suswanto (Institut Bisnis Muhammadiyah Bekasi, 2023)
Abstract This study aims to determine the effect of the Canva application on visual communication desain creativity in SCTV 2023 internship students. The data collection method used in this study was a questionnaire. The population in this study were 2023 SCTV internship students. The sampling technique used was purposive sampling with a sample size of 70 respondents. data analysis methods used are validity test, reliability test, normality test, linearity test, simple linear regression analysis, partial significant test (T) and determination coefficient test (R- Square) using the SPSS 25 application. The results of this study state that t count> ct table (10.478> 1.667), namely H0 is rejected, H1 is accepted, and the results of the significance test of 0.00 < from the alpha value (a) 0.1 which means that there is an effect of the Canva application on visual communication desain creativity.. Keyword: Graphic Desain Media, Canva Application, Creativity, Visual Communication Desain